PEMBERDAYAAN PENDIDIKAN MELALUI PROGRAM PARIAMAN CERDAS OLEH BAZNAS KOTA PARIAMAN - Nur Alhidayatillah; Ica Marlisa (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2020)
BAZNAS Pariaman City is one of the institutions which aims to receipt and distribution zakat funds. It also has a role to enhance quality education, in particular, for impoverished communities to continue their study. Quality education will influence communities' mindset and behavior in the future so that it takes seriousness from related institutions to play a role in this field. This research focuses on how to empower education carried out through a program called the Program Pariaman Cerdas by BAZNAS Pariaman City. This research uses qualitative methods by describing the phenomena that occur in the field and analyzed them in depth. Data collection methods used were interviews, observation, and documentation. This study reveals that BAZNAS has a specific role in empowering education through the Program Pariaman Cerdas. It has shown through the three programs carried out by BAZNAS in its empowerment processes such as consumptive zakat empowerment, creative consumptive zakat empowerment, and creative productive empowerment.